BIPV in India: Opportunities, challenges, and pathways for urban planning and smart cities - Kedar Mehta; Ravita Lamba; Sunanda Sinha; Nand Kumar (Solar Compass, 2025)
As India urbanizes rapidly, sustainable energy solutions have become a priority to meet rising energy demands and mitigate environmental impacts. Building-Integrated Photovoltaics (BIPV) offer a promising approach to harness solar energy within urban infrastructure, transforming buildings into renewable energy assets. Unlike conventional rooftop PV systems, BIPV maximizes urban space utilization while enhancing architectural aesthetics and energy efficiency. However, the adoption of BIPV in India remains limited due to factors such as regulatory barriers, lack of standardized designs, and high initial costs. This study uses SWOT (Strengths, Weaknesses, Opportunities, Threats) and TOWS (Threats, Opportunities, Weaknesses, Strengths) analyses to assess the potential, opportunities, and challenges of BIPV in India’s urban planning. It then discusses policy implications and offers practical recommendations for implementation in Indian cities. Key findings of this study indicate that BIPV adoption in India can significantly contribute to urban sustainability by reducing carbon emissions, improving energy self-sufficiency, and lowering long-term operational costs. The SWOT and TOWS analysis reveal that while BIPV presents opportunities for smart urban integration, challenges such as high initial investments and lack of awareness must be addressed through targeted policies and incentives. Additionally, global case studies highlight successful BIPV implementations, providing valuable lessons for India’s urban planning strategies.